(untitled) (SAARC Journal of Agriculture, 2025)
The study aimed to investigate the effects of chitosan-based zinc oxide and silver nanoparticles coating on physicochemical properties of papaya and to optimize nanoparticles concentrations for extending its postharvest shelf life. The experiment was conducted in February, 2022 at the Institute of Agriculture and Animal Science (IAAS), Tribhuvan University, Kathmandu, Nepal, using a Completely Randomized Design (CRD) with nine treatments and three replications. The treatments consisted of different concentrations (50 ppm, 100 ppm, 150 ppm, and 200 ppm) of either Zinc oxide and silver nanoparticles, along with a control. Zinc oxide and silver nanoparticles were synthesized from banana peel extract and the average crystalline sizes were found to be 22.30nm and 4.46nm, respectively. Fruits were dipped in 1.5% (w/v) chitosan with 50–200 ppm of zinc oxide and silver nanoparticles and then stored at ambient temperature (14±1.6°C) and 75% RH. The nanoparticles coatings slowed changes in total soluble solids (TSS) and total titratable acidity (TTA), delaying ripening. Treated fruits showed reduced physiological loss in weight and maintained firmness better than control, with firmness decreasing to 4.79 kg in untreated fruits compared to 7.35 kg in coated fruits on 18th day of storage. Coated fruits retained more ascorbic acid, and the storage life increased by 8 and 9 days with 150 and 200 ppm treatments, respectively. However, consumer preference declined for concentrations above 150 ppm. Thus, 100–150 ppm chitosan-based zinc oxide/silver nanoparticles are found to be effective for extending shelf-life and maintaining physiochemical characteristics of papaya. However, its residual and health-related dimensions need to be extensively studied before its commercial application. SAARC J. Agric., 22(2): 181-196 (2024)